Geometrical changes in iron(III) complexes caused by the replacement of phenyl groups in the ligand triphenylphosphine oxide by benzyl radicals - Klein, Stanlei Ivair; Massabni, Antonio Carlos; Moreira, José Celso; Tancredo, Aldo (Eclética Química, 1988)
.